Konsep Kepemimpinan Musa Terhadap Pola Kepemimpinan Kristen Di Era Digital - Nofrianus Zalukhu; Claudia Angelina; Monica Santosa (STTI Harvest Semarang, 2022)
This research was raised based on the consequences of the phenomenon of the loss of identity of Christian leaders in today's digital era. This condition was actually born from the unpreparedness of leaders in taking advantage of the digital era to develop themselves into leaders who have character and have spiritual values. Through these conditions, this study tries to analyze a